1969
DOI: 10.1002/cjce.5450470206
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of packed beds — A review

Abstract: Some structural properties of packed bed systems on both the local and overall scales which are available in the literature and of interest in chemical engineering applications are discussed. Regular and random packings of uniformly sized spheres are initially analyzed as a basis for the later examination of the more general case of random packed beds containing particles of various sizes and shapes, with or without restraining surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(88 citation statements)
references
References 153 publications
7
79
0
Order By: Relevance
“…This mean value is in good agreement with that obtained by Kato et al (6) In general, random packings are separated into three categories (10) . "Very loose random packing" is obtained when momentum is minimized and opportunities for bridging are maximized.…”
Section: Case Of No Wall/floor Effectsupporting
confidence: 91%
“…This mean value is in good agreement with that obtained by Kato et al (6) In general, random packings are separated into three categories (10) . "Very loose random packing" is obtained when momentum is minimized and opportunities for bridging are maximized.…”
Section: Case Of No Wall/floor Effectsupporting
confidence: 91%
“…It is shown that the present packings fall in the category of random loose packing [16,17]. In addition, since this value is very close to the value (41%) obtained for the most slightly sintered glass-bead aggregates by experiments [18], the present packing method is justified even though various simplifying assumptions have been made, including negligence of the acceleration term in the motion equation.…”
Section: Porositysupporting
confidence: 77%
“…Beveridge [20] and are presented in Table 3.3. Table 3.3 Four modes of particle packing as listed by Haughey and Beveridge [20].…”
Section: Effect Of the Microporous Coating Thickness On Wickabilitymentioning
confidence: 99%